Plankton and benthos in Lake Blagodatnoye (Iturup Island) in summer - V. S. Labay; I. V. Motylkova; D. S. Zavarzin; A. V. Litvinenko; I. A. Atamanova; E. V. Abramova; O. N. Berezova; T. S. Shpilko; A. I. Vodop’janova; O. B. Sharlay (Известия ТИНРО, 2024)
Lake Blagodatnoye is an oligohaline meromictic reservoir with the two-layer vertical structure — a typical lagoon lake for the southern Far East of Russia. Its upper layer is occupied by fresh water and the lower layer — by brackish water. The greatest warming of water (up to 22 оC) is observed at the lake surface in late July — early August. In total, 274 species are found in phytoplankton of the lake that is the largest number among all surveyed lagoon lakes in the south of Sakhalin-Kuril region. Bacillariophyta form the basis of the phytoplankton species composition (64 % of species). Abundance and biomass of the phytoplankton vary widely from 1.15 . 106 to 160.44 . 106 cells/L and from 0.41 to 6.14 g/m3, respectively. Several peaks are noted in seasonal dynamics of these indices. Zooplankton in the lake includes 25 species. All these species are typical for lagoon lakes in the south of Sakhalin-Kuril region. Wide variations in abundance and biomass are noted for the zooplankton: from 10550 to 99350 ind./m3 and from 47.1 to 231.0 mg/m3, respectively. Two types of species composition are identified in the summer succession of the phytoand zooplankton communities. The phytoplankton groups change at the border between June and July, when temperature at the surface passes the value of 14–16 оC. The key species of the early-summer phytoplankton are Cyanobacteria of genera Aphanocapsa, Chroococcus, Microcystis, Anabaena and Bacillariophyta of the genus Asterionella, whereas Aulacoseira granulata and A. granulata var. angutissima are the most abundant in late summer. For zooplankton, the boundary between the early-summer and late-summer seasons is shifted to middle July when the water temperature rises to 17–18 оC. Rotifera of Asplanchna priodonta, Cladocera of Bosmina sp., younger copepodites of Cyclops and Eurytemora caspica tethysiana dominate in early summer, whereas Bosmina sp. and juveniles of Cyclops — in late summer. Macrozoobenthos in the lake is represented by 25 species of invertebrates. The basis of species diversity is formed by amphibiotic insects. Number of species and total distribution density and biomass of macrozoobenthos mostly declined with the depth: there were 18 species, 370 ± 50 ind./m2, 3.023 ± 0.459 g/m2 in the intertidal zone, 14 species, 580 ± 59 ind./m2, 3.477 ± 0.447 g/m2 in the elittoral zone, and 10 species, 364 ± 36 ind./m2, 2.110 ± 0.248 g/m2 in the profundal zone, and dominant species were changed from Amphipoda Eogammarus barbatus in the intertidal zone to Chironomidae Chironomus dorsalis in the elittoral zone and to Gastropoda Cincinna japonica, Oligochaeta Lumbriculus variegatus and Chironomidae C. dorsalis in the profundal zone. The phytoplankton production in the coastal zone (depth of 0–3 m) was estimated as 552.86 kcal/m2 in June-August. Zooplankton consumed only 0.7 % of this production and produced 767 cal/m2. The production of non-predatory zoobenthos was 8644 cal/m2, with the inputs of 70.2 % for detritus feeders of 70.2 %, 11.8 % for macroalgae feeders, 11.6 % for deposit feeders, 5.8 % for grazers, and 0.6 % for filtered suspension feeders. A part of this production (6.9 %) was transmitted to the feed of carnivorous zoobenthos, so 8286 cal/m2 of the macrozoobenthos production could be used for fish feeding in the coastal zone. The phytoplankton production in the open waters (depth of 3–9 m) was estimated in 2580 kcal/m2. Zooplankton consumed 1.01 % of this production and produced 3578 cal/m2. The production of non-predatory zoobenthos in this zone was 6179 cal/m2 (detritus feeders 68.1 %, deposit feeders 18.8 %, grazers 6.6 %, macroalgae feeders 3.0 %, and filtered suspension feeders 3.5 %). The portion of 12.7 % of this production was transmitted to the feed of carnivorous zoobenthos. The total macrozoobenthos production in the open waters was 5708 cal/m2. The total reserve of food for fish, including zooplankton and benthos, was evaluated in 9286 cal/m2.